Lung function prior to viral lower respiratory tract infections in prematurely born infants. Issue 6 (28th March 2011) - Drysdale, Simon B; Wilson, Theresa; Alcazar, Mireia; Broughton, Simon; Zuckerman, Mark; Smith, Melvyn; Rafferty, Gerrard F; Johnston, S L; Greenough, Anne
Abstract : Objective: Prematurely born infants who develop respiratory syncytial virus (RSV) lower respiratory tract infections (LRTIs) have lung function abnormalities at follow-up. The aim of this study was to determine whether prematurely born infants who developed symptomatic RSV, or other viral LRTI(s), had poorer premorbid lung function than infants who did not develop LRTIs during the RSV season. Methods: Lung function (functional residual capacity (FRC), compliance (Crs) and resistance (Rrs) of the respiratory system) was measured at 36 weeks postmenstrual age. After neonatal unit discharge, nasopharyngeal aspirates were obtained whenever the infants had an LRTI, regardless of whether this was in the community or in hospital. Nasopharyngeal aspirates were examined for RSV A and B, rhinovirus, influenza A and B, parainfluenza 1, 2 and 3, human metapneumovirus and adenovirus. Results: 159 infants with a median gestational age of 34 (range 23–36) weeks were prospectively followed. 73 infants developed LRTIs: 27 had at least one RSV LRTI and 31 had at least one other viral LRTI, but not an RSV LRTI. Overall, there were no significant differences in the FRC (p=0.54), Crs (p=0.11) or Rrs (p=0.12) results between those who developed an RSV or other viral LRTI and those who did not develop an LRTI. Infants with RSV or other viral LRTIs who were admitted to hospital compared with those who were not had higher Rrs results (p=0.033 and p=0.039, respectively). Conclusion: Diminished premorbid lung function may predispose prematurely born infants to severe viral LRTIs in infancy.